IVIM DW-MRI of autoimmune pancreatitis: therapy monitoring and differentiation from pancreatic cancer - Klauß, Miriam; Maier-Hein, Klaus H.; Tjaden, Christin; Hackert, Thilo; Grenacher, Lars; Stieltjes, Bram (European radiology, 2016)
To evaluate IVIM DW-MRI for changes in IVIM-derived parameters during steroid treatment of autoimmune pancreatitis (AIP) and for the differentiation from pancreatic cancer (PC).